Assessing the Victim-Offender Overlap Among Adolescents in Rural China - Cheung, Nicole W. T. (Crime & delinquency, 2023)
Grounded in criminological theories (routine activity, social bonding, social disorganization, control balance, differential association, and general strain), this study extended the victim-offender overlap research by considering the specificity of rurality. We collected data from 2,839 adolescents in rural China and applied multilevel item response theory modeling. Both victim-offender overlap and differentiation were evident among rural adolescents. The victimization-offending overlap was associated with unstructured socializing, family and neighborhood control, moral beliefs, peer delinquency, and certain forms of social strain (loss of positively valued stimuli and exposure to negative stimuli). The differential tendency toward victimization over offending was a function of non-deviant solitary routines, failure to achieve positively valued goals, and strain-specific depression. The insignificance of control imbalance may need clarification of its conceptual relevance to rurality.